MANAJEMEN DIET TIDAK MEMPENGARUHI KUALITAS HIDUP PASIEN GGK DENGAN HEMODIALISIS - Susanita, Nancy; Pardede, Lisbeth; Agustina Nursafitri , Irma (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Efforts in diet management and adherence the prescribed diet are crucial for CKD patients undergoing hemodialysis. Effective diet management can prevent complications and recover the quality of life.  The aims in this study is to analyze the relationship the knowledge level in diet management and quality of life those undergoing hemodialysis process in Hemodialysis Room of Bekasi Private Hospital. This study has a relationship descriptive design using method a cross-sectional approach. Sample consists of 40 CKD patients undergoing hemodialysis, through total sampling technique. Data were processed in tabular form and described to show the relationship between knowledge levels also diet management in chronic renal failure patients undergoing hemodialysis. The study results show that patients with good knowledge with good quality of life, there are 12 respondents (32.4%), moderate quality of life with 25 respondents (67.6%), and no respondents with poor quality life. Patients in sufficient knowledge have quality life one respondent each for good is 33.3%, moderate is 33.3% and poor is 33.3%. Chi-square test yielded a p-value is 0.104. The research concludes that there is no significant correlations between level of knowledge about diet management and the quality of life of CGK patients who undergoing hemodialysis.  Recommendation for next study is take more bigger sample and add how longtime patient get hemodialysis as inclusion criteria.